The Impact of Supply Chain Social Capital on Market Orientation: The Buyer Perspective - Mohd Hanafi Azman Ong; Norazlina Mohd Yasin (International Journal of Supply Chain Management, 2020)
Developing the strength of social ties between buying and supplying organizations is increasingly cited as a critical differentiator of high and low performers in global supply chains. While the creation of relational capital within an organization is a relatively well-identified concept in organizational research, comparatively little research exists on the bonding and bridging social ties that create relational value in supply chains. In our research, we extend theoretical models of group social conduits into this context and develop a model that posits the impact of social capital on the reactive and proactive market orientation between buyers and suppliers. Results from our study of 114 technology-based companies in Malaysia suggest that formal social capital are important in the creation of relational capital, which in turn can lead to improving market orientation eventually supplier relationship outcomes. Formal bridging social capital conduits appear to play a lesser role in deriving these benefits.